Modelling winter survival mating and trapping of Queensland fruit fly in Auckland New Zealand - Kean, J.M. (New Zealand Plant Protection, 2016)
In February 2015 an established population of the Queensland fruit fly (Qfly Bactrocera tryoni) was detected in Grey Lynn Auckland It was questionable whether Qfly might successfully overwinter in Auckland and how trap efficacy and mating behaviour would be affected by winter conditions During the official biosecurity response to eradicate Qfly these questions were addressed using published Qfly models that had been developed and parameterised from biological data from its native range A model for cold acclimatisation suggested that Auckland winters would not be sufficiently cold to cause significant mortality of adult Qfly but substantial cold mortality might occur in more southern locations The temperature requirement for mating suggested mating would be relatively rare from June to October and two models for relative trap efficacy suggested that traps would be relatively ineffective until late spring (OctoberNovember) The Ministry for Primary Industrys biosecurity response was successful with no detection of Qfly after March 2015 and eradication formally declared in December 2015